HUBUNGAN KELENTUKAN DAN POWER OTOT TUNGKAI TERHADAP KETEPATAN SERVIS PADA CLUB SEPAK TAKRAW SMA NEGERI 1 BENAI KABUPATEN KUANTAN SINGINGI - Pontas Pamela; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: based on study from the sepak takraw athletes of SMA Negeri 1 Benai district, there are still many players who experience errors while serving. Failures that often occur during maintenance, such as: the legs are too stiff and not quite right when maintenance is performed on the opponent's area and very slowly to pass the ball during maintenance. It is suspected that the causal factor is the physical condition of the athlete. The test in this study was to determine the relationship between leg muscle strength and limb extension with sevis accuracy in takraw athletes at Benai 1 High School, Kuantan Singingi. The population in this study consisted of all male football athletes from SMA Negeri 1 Benai, Kuantan Singingi district, who were 10. The sample in this study was 10 people with total sampling techniques. The instruments in this study are front split, vertical jump and service accuracy. The data obtained were analyzed using the current product correlation. Based on the analysis of normality test data, X1 produces Lcount of 0.2324 and Ltable 0.256 and X2 produces Lcount of 0.1580 and Ltable 0.256. while the Y variable yields Lcount of 0.1962 and Ltable of 0.258. This means that Lcount <LTable. The data is normally distributed based on statistical data analysis. Based on the analysis of test requirements above, the hypothesis test on variables X1 and X2 against the Y-variable data is 0.573> 0.666 Rcount> Rtable data. There is therefore no joint relationship between limb extension and leg muscle strength with the accuracy of the service for takraw athletes. Benai 1 High School, Kuantan Singingi Regency.Key Words: Leg extension, Leg Muscle Power, Service Accuracy